1994
DOI: 10.1152/ajpheart.1994.266.5.h1722
|View full text |Cite
|
Sign up to set email alerts
|

GABAB receptor-mediated mechanisms in the RVLM studied by microinjections of two GABAB receptor antagonists

Abstract: The cardiovascular effects of microinjections of two gamma-aminobutyric acid (GABA) antagonists specifically acting on GABAB receptors, 2-hydroxy-saclofen (2-OH-S) and CGP-35348, into vasopressor sites of rostral ventrolateral medulla (RVLM) were studied in rats anesthetized with urethan. Bilateral microinjection of 2-OH-S induced significant increases in mean arterial pressure (MAP) and heart rate (HR) in 21 of 26 RVLM vasopressor sites (81%); average increases obtained in the 26 sites studied were +25.2 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…However, in the same animals, the fall in blood pressure was greater after urethane anesthesia (15). Either GABA A receptor antagonists (bicuculline) or GABA B receptor antagonists (2-hydroxysaclofen or CGP-35348) microinjected in the RVLM produced a pressor response in urethane-anesthetized rats (1,5), suggesting that, at least in the RVLM, urethane is not producing inhibition of the tonic activity of GABAergic neurons projecting to this region. However, no experiments with the use of patch-clamp recordings were performed to explore the effect of urethane on RVLM neurons.…”
Section: Discussionmentioning
confidence: 86%
“…However, in the same animals, the fall in blood pressure was greater after urethane anesthesia (15). Either GABA A receptor antagonists (bicuculline) or GABA B receptor antagonists (2-hydroxysaclofen or CGP-35348) microinjected in the RVLM produced a pressor response in urethane-anesthetized rats (1,5), suggesting that, at least in the RVLM, urethane is not producing inhibition of the tonic activity of GABAergic neurons projecting to this region. However, no experiments with the use of patch-clamp recordings were performed to explore the effect of urethane on RVLM neurons.…”
Section: Discussionmentioning
confidence: 86%
“…The observed increase in B1a expression in the VLM of SHR is interesting, as there is evidence that GABA B receptors may have a function in blood pressure regulation by inhibiting the activity of bulbospinal sympathetic premotor neurones of the rostral VLM (Amano and Kubo 1993;Avanzino et al 1994;Li and Guyenet 1995). In a previous immunohistochemical study, it was found that 95% of the C1 catecholamine neurones of the rostral VLM, believed to have an important role in blood pressure regulation (Guyenet 2006), expressed B1 subtype immunoreactivity and 86% expressed B2 immunoreactivity (Burman et al 2003).…”
Section: Changes In Gaba B Expression In the Shrmentioning
confidence: 88%
“…The paraventricular nucleus and the rostral ventrolateral medulla are known to be responsible for controlling the sympathetic outflow (Coote, 2005;Tjen-A-Looi et al, 2009). The microinjection of GABA or GABA receptor agonist into the rostral ventrolateral medulla or paraventricular nucleus decreased blood pressure by inhibiting sympathetic nerve activity (Avanzino et al, 1994;Li and Pan, 2007). Durgam et al (1999) reported that the microinjection of the GABA receptor agonist into the nucleus of the solitary tract, which is known to be central regulator for baroreflex, increased blood pressure by enhancing the sympathetic outflow.…”
Section: Downloaded Frommentioning
confidence: 99%